VALUASI EKONOMI EKOWISATA KEBUN RAYA MANGROVE SURABAYA GUNUNG ANYAR - Putri, Deanisa Herawati; Yektiningsih, Endang; Rozci, Fatchur (Lambung Mangkurat University-Indonesia, 2024)
Surabaya Mangrove Forest Park is not only a natural beauty attraction for visitors but also provides economic benefits for the surrounding community. This study aims to analyze the economic value of ecotourism in the park, understand the factors that influence the number of tourist visits, and determine the willingness of the community to pay for the existence of this park. Research data was collected from 60 park visitors using quota sampling techniques. Multiple linear regression analysis and the Contingent Valuation Method (CVM) were used to examine the factors influencing tourist visits and willingness to pay. The results of the study show that travel costs are a significant factor influencing the number of tourist visits. The economic value of ecotourism in Surabaya Mangrove Forest Park reaches Rp 10.828.609.000 /year (ITCM) and Rp 15.598.117.400 (CVM). The average community's willingness to pay for the existence of this park is Rp 5.050. The findings of this study confirm that Surabaya Mangrove Forest Park has significant ecotourism economic value. Sustainable ecotourism development in this location can provide economic and environmental benefits for the surrounding community.